PERANCANGAN PETA DIGITAL BERBASIS WEB DI UNIVERSITAS ISLAM NEGERI SULTHAN THAHA SAIFUDDIN JAMBI - Ningrum, Linda Sekartaji; Huda, Imam Arifa’illah Syaiful; Putri, Utami Mizani (Information Technology Education Department, 2024)
This research discusses the design of a WebGIS-based Geographic Information System at Sulthan Thaha Saifuddin Jambi State Islamic University using digital maps. The goal is to produce a Digital Map at Sulthan Thaha Saifuddin Jambi State Islamic University based on WebGIS which includes various displays such as Home, profile, map, information, and contact. The method used is a structured and phased waterfall system development model. The application of digital maps provides advantages in displaying data, images, animations, and internet connectivity that are useful for new discoveries and innovations. The results of the study produced a WebGIS-based Geographic Information System that provides information about the location of buildings and information at Sulthan Thaha Saifuddin Jambi State Islamic University through a display that has been designed. This system helps users access information easily and efficiently. This WebGIS-based digital map design has a significant contribution in increasing the accessibility of geographic information, as well as making the research and innovation process more effective and efficient. Based on the data obtained from the results of the questionnaire distributed, it is categorized as very feasible to use.